Sediment Yield Estimation Using Gis-Based Sediment Production Rate (Spr) Approach: A Study Of Kunhar River Basin, Pakistan - Zahida Akhtar , Muhammad Jamal Nasir , Zahid Ali , Sardar Muzaffar Hussain Zahid , Shahid Iqbal , Zahid Khan (Migration Letters, 2024)
The Kunhar River basin (KRB) in Mansehra district, Pakistan, faces significant challenges due to soil erosion. The current study focuses on analyzing sediment production rates (SPR) in the Kunhar River basin using geographic information systems (GIS). ASTERG DEM (V3) with a spatial resolution of 30m acquired from NASA Earthdata (ASTER Global Digital Elevation Map (nasa.gov) serve as the primary source of data. The sub-basin form factor (Rf)), (Circulatory Ratio (Rc) and (Compactness Coefficient Cc) ̇ were derived using the Horton’s (1945), Smith (1957), and Strahler (1964) outlined approach, in the Arc GIS 10.8 software environment. Findings reveal widespread sediment production across the basin, with certain sub-basins showing notably high rates. Th[1]e analysis reveals that the sediment production from KRB is ranging from 0.346 to 0.578 ha-m/100 km2/year. At sub-basin level Sb-2, SB5, SB-6, SB-9, and SB-18 (24% KR sub-basins) experienced very high sediment production rate. Likewise, 11 sub-basins (52% of the KR sub-basins) i.e. SB-1, SB-4, SB-11, SB-12, SB-13, SB-14, SB-15, SB-16, SB-19, SB-20, and SB-21 have reported high levels of sediment production. The two sub-basins SB-7 and SB-8, (10% of the KR sub-basins), have a moderate sediment production rate; while; SB-3, SB-10, and SB-17, (14% of the KR sub-basins) have a low sediment production rate. These findings are crucial for policymakers and relevant organizations in making informed decisions to combat soil erosion and its adverse effects on water resources, agriculture, and infrastructure. The analysis marks a crucial step toward comprehensive watershed management strategies aimed at preserving the ecological integrity and socioeconomic resilience of the Kunhar River basin and similar hydrological systems nationwide.